Respuesta :

Answer:

The correct answer should be:

[tex]y=\frac{1}{2}(e^3+1)\text{ or } y=\frac{e^3}{2}+\frac{1}{2}[/tex]

Step-by-step explanation:

We have the equation:

[tex]\ln(2y-1)=3[/tex]

Let’s remove the natural logarithm by raising both sides to e. This yields:

[tex]e^{\ln(2y-1)}=e^3[/tex]

The left will simplify to:

[tex]2y-1=e^3[/tex]

Add 1 to both sides:

[tex]2y=e^3+1[/tex]

Divide both sides by 2. So, the value of y should be:

[tex]y=\frac{1}{2}(e^3+1)[/tex]

Answer:

The correct answer is indeed y = [tex]\frac{e^3+1}{2}[/tex]

Step-by-step explanation:

I also took the test!